Ideological rhetoric: a critical discourse analysis of Prabowo’s first inauguration speech - Hariati, Puji; Purwarno, Purwarno (JOALL (Journal of Applied Linguistics and Literature), 2025)
This study examines the rhetorical strategies, ideological rhetoric, and political ideology of nation-building presented by Prabowo Subianto in his inauguration speech as the newly elected president of Indonesia on October 20, 2024. Using a descriptive qualitative approach, the analysis is grounded in Critical Discourse Analysis (CDA) to reveal the underlying rhetorical devices and ideological themes conveyed in his speech. The study is structured through two interlinked dimensions: rhetorical strategies and ideological rhetoric, utilizing Aristotle’s rhetorical concepts of ethos, pathos, and logos to provide a comprehensive interpretation of the speech. The analysis addresses key themes such as sovereignty, the relationship between the state and its citizens, justice, equality, the vision of a "Great Indonesia," the plight of wong cilik (the ordinary people), and the cultural principle of gotong royong (cooperation). These themes are pivotal to Prabowo’s articulation of Indonesia's identity and vision for the nation’s future. Findings reveal that Prabowo employs a balanced array of rhetorical strategies, ethos, and pathos, accounting for approximately 30% of the speech, focusing on his credibility and emotional connection with the audience. Logos, comprising 40% of the rhetoric, underscores logical and structured arguments, enhancing his appeal to rational thought. The ideological rhetoric, meanwhile, emphasizes national sovereignty, justice, and unity, reflecting Prabowo’s deep-seated vision for an independent and resilient Indonesia. His ideology resonates with themes of independence and self-reliance, advocating a stance against foreign influence, and drawing from Indonesia’s historical struggles for independence. This study sheds light on how Prabowo's rhetorical strategies and ideological expressions serve to frame political discourse and contribute to the formation of national identity, underscoring the role of presidential rhetoric in shaping the public's perception of leadership and vision for Indonesia.